بلاغــــة التَّتْمِيم والتكميـــــــل في القـــــــرآن الكريـــــــــــــــــــــم - قيطون, قويدر (جامعة الوادي - University of Eloued, 2016)
يعرض هذا المقال لأسلوبين بلاغيين متميّزين ، لهما أثرهما الواضح في تجويد الخطاب ، وتصحيحه ، ودقته ، ولا تقف فائدتهما عند ضبط النص ، وحسن إحكامه فقط ؛ بل نجد لهما إضافة متميّزة على مستوى جمالية الخطاب ، بما يضفيانه عليه من فنية وروعة لها أثرها البالغ على المتلقي. ونحن نعرض لهذين الأسلوبين معا لأنهما متداخلان متلازمان ، استعملتهما العرب ، وعلى سَننها جاء الخطاب القرآني المعجز ، الذي نحاول أن نقف عند بلاغية هذين الأسلوبين فيه. Summary This article presents two distinctively eloquent styles; their impact is clear in perfecting the speech, and determining the accuracy. They are not useful when adjusting the text and its provisions only; but they add the distinguished level of the aesthetic discourse, as they give it the artistic splendor which in turn has its impact on the recipient. We highlight these two styles because they are intrinsically interconnected, as used (employed) by the Arabs; and in the same fashion, they are present in the Miraculous Qur’an through which we investigate their eloquence.
مقال
Keywords: بلاغــــة ؛التَّتْمِيم ؛التكميـــــــل ؛ القـــــــرآن الكريـــــــــــــــــــــم